PENGARUH MODEL PROBLEM BASED LEARNING BERBANTUAN KOMIK DENGAN TEMA KEBERAGAMAN BUDAYA TERHADAP KEMAMPUAN BERPIKIR KRITIS PESERTA DIDIK SEKOLAH DASAR - Marlinda, Dea; Luthvi Azizah, Alif; Fernando Rizqi, Yoga; Destini, Frida (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the influence of the Problem Based Learning (PBL) model assisted by comic media with the theme of cultural diversity on the critical thinking ability of elementary school students. The study used a pre-experimental method with a One Group Pretest-Posttest design. The research sample amounted to 28 students in class IVB of SD Negeri 4 Sukadamai. Data was collected through critical thinking skills tests and observation sheets. Data analysis used the N-Gain test and paired sample t-test. The results showed a significance value of 0.001 (<0.05) and an average N-Gain of 0.77 in the high category. These results show that the application of the PBL model assisted by comic media has a significant effect on students' critical thinking skills